Preterm Birth and ADHD in School Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Karolinska Institutet, Sachs Children's Hospital, Stockholm, and Uppsala and Stockholm Universities, Sweden, analyzed the effect of moderate and extreme preterm birth on the risk for ADHD in school age children who have survived from NICUs, and allowing for genetic, perinatal, and socioeconomic confounders.